Optimizing the Integration of Meaningful, Mindful, and Joyful Learning in Physical Education: Creating Immersive and Enjoyable Learning Experiences (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Traditional teacher-centered approaches continue to dominate physical education, which restricts active participation and diminishes student motivation. These methods are less effective in supporting holistic development, especially in post-pandemic settings that require innovative, student-centered strategies. despite this necessity, there exists a deficiency of thorough empirical study about the implementation of deep learning in physical education. This study investigates the efficacy of incorporating Meaningful, Mindful, and Joyful (M-M-J) Learning in physical education to improve student engagement and academic performance. A quasi-experimental design featuring a non-equivalent control group pretest–posttest was conducted with 100 eighth-grade students in Sorong City. The experimental group received instruction using the M-M-J Learning approach, while the control group followed conventional methods. Both groups had pretest and posttest evaluations.  Quantitative data were examined utilizing gain scores, t-tests, and Cohen’s d.  Qualitative reflections yielded supplementary insights. The experimental group attained superior posttest results (M = 83.10) compared to the control group (M = 64.80), exhibiting a substantial effect size (d = 4.95).  Qualitative research also shown heightened motivation and classroom engagement. Conclusion: The M-M-J approach was more effective than traditional methods. These results support curriculum innovation that fosters active, reflective, and enjoyable learning, and present a promising model for post-pandemic physical education.